Conjunctival ultraviolet autofluorescence area decreases with age and sunglasses use. Issue 5 (23rd November 2021) - Lingham, Gareth; Kugelman, Jason; Charng, Jason; Lee, Samantha SY; Yazar, Seyhan; McKnight, Charlotte M; Coroneo, Minas T; Lucas, Robyn M; Brown, Holly; Stevenson, Louis J; Mackey, David A; Alonso-Caneiro, David
Abstract : Background: Conjunctival ultraviolet autofluorescence (CUVAF) is a method of detecting conjunctival damage related to ultraviolet radiation exposure. In cross-sectional studies, CUVAF area is positively associated with self-reported time spent outdoors and pterygium and negatively associated with myopia; however, longitudinal studies are scarce. Aims: To use a novel deep learning-based tool to assess 8-year change in CUVAF area in young adults, investigate factors associated with this change and identify the number of new onset pterygia. Methods: A deep learning-based CUVAF tool was developed to measure CUVAF area. CUVAF area and pterygium status were assessed at three study visits: baseline (participants were approximately 20 years old) and at 7-year and 8-year follow-ups. Participants self-reported sun protection behaviours and ocular history. Results: CUVAF data were available for 1497 participants from at least one study visit; 633 (43%) participants had complete CUVAF data. Mean CUVAF areas at baseline and the 7-year and 8-year follow-ups were 48.4, 39.3 and 37.7 mm 2, respectively. There was a decrease in mean CUVAF area over time (change in total CUVAF area=−0.96 mm 2 per year (95% CI: −1.07 to –0.86)). For participants who wore sunglasses ≥1/2 of the time, CUVAF area decreased by an additional −0.42 mm 2 per year (95% CI: −0.72 to –0.12) on average. Fourteen (1.5%) participants developed a pterygium. Conclusions: In this young adult cohort, CUVAF area declined over an 8-year period. Wearing sunglasses was associated with a faster reduction in CUVAF area. Deep learning-based models can assist in accurate and efficient measurement of CUVAF area.